Reactive natural phosphate enriched with filter cake enhances soil P content and noni seedlings growth - Caione, Gustavo; Silva Campos, Cid Naudi; Agostinho, Flavia Bastos; Moda, Leandro Rosatto [UNESP]; Prado, Renato de Mello [UNESP]; Barreto, Rafael Ferreira [UNESP] (Taylor & Francis As, 2018)
One of the major challenges in crop production is increase efficiency of non-renewable P sources, or replace them with renewable sources. The objective of this study is to evaluate the effects of phosphorus (P) fertilization using reactive natural phosphate, filter cake, peat and biofertilizer on soil P content, foliar P content and growth of noni seedlings. The treatments were: control (without P fertilization); phosphorus; filter cake; phosphorus+filter cake; phosphorus+filter cake+peat; and phosphorus+filter cake+peat+biofertilizer. All treatments were replicated four times and arranged in a completely randomized design. The treatments phosphorus+filter cake; phosphorus+ filter cake+peat; and phosphorus+filter cake+peat+biofertilizer increased phosphorus content in soil and in leaf, and the growth of noni seedlings. Our results indicates that natural reactive phosphate enriched with filter cake can be used as phosphate fertilizer on noni seedlings cultivation.
Keywords: Medicinal plant; Morinda citrifolia; phosphate fertilizer; rubiaceae; renewable P sources